Ethnography is not qualitative. Issue 1 (2nd January 2020) - Walford, Geoffrey
ABSTRACT: This article looks back at several of the classic ethnographies in British sociology of education and shows that quantitative work played a significant part in many of them, and that quantitative results were part of the evidence used to support claims and arguments put forward by the authors. The article then examines some more recent ethnographies and shows that quantitative research within them has dwindled. It is then claimed that the artificial division between quantitative and qualitative research in education has made research poorer, and that the categorisation of ethnographic research as qualitative has been detrimental to ethnography. Some ways in which more quantitative work could (and often should) be included are then suggested.